Unknown Аrchaic Тranslation of Sermon 5 from John of Sinaya’s Scala Paradisi, in a Serbian Manuscript from the 14th Century - Спасова, Мария (Poznańskie Studia Slawistyczne, 2018)
The subject of this research is an unknown Slavic translation of Sermon 5 John of Sinaya’s Scala Paradisi (Lestvica) in a Serbian Menaion and Triodion Panagyric, rewritten from an old Bulgarian antigraph which has preserved the archaic grammatical traits of the prototranslation. In the sermon’s text, forms of asigmatic aorist and first sigmatic aorist with a preserved “s” are being registered, as well as non-contrahered forms for imperfect, forms of past active I participle formed with suffix -ьш- from verbs with a base ending on -и-, possessive adjectives as a translation of the Greek genitive case for possession, usage of a local prepositionless, excessive prepositionless usage of ablative case, descriptive future with a preponderance of forms of хотѣти + infinitive, dual number forms, non-contrahered forms of complex (determinative) adjectives, etc. The translation of the sermon of the transcript in NHM24 includes rare lexemes that attribute it to the early translations of Cyril and Methodius. It demonstrates similarities to the Glagolitic translations of the hand-written cannon of 10th–11th century.